PENGGUNAAN BENTUK REDUPLIKASI DALAM NOVEL SELAMAT TINGGAL KARYA TERE LIYE - Supriyati Supriyati; Putri Silvia Anisa (Universitas Batanghari, 2022)
The purpose of this research was to describe reduplication form in Selamat Tinggal novel by Tere Liye. This research includes a type of qualitative descriptive research described in findings in the form of quotes contained in Selamat Tinggal novel by Tere Liye. In this research, the data is taken from quotes containing the entire form of reduplication, partial reduplication, reduplication with the affixation and reduplication derived from phoneme changes. This type of qualitative descriptive research is a step to describe the use of reduplication in this novel. The results of this research can be concluded that four forms of reduplication use are found in the Selamat Tinggal novel by Tere Liye. Of the findings of 110 quotations based on the four uses of the form of redulication in the novel, the most dominant is the form of reduplication combined with the process of establishing the affix found as many as 51 quotations and the less one is redulication with phoneme changes amount to 7 quotations. While the total reduation was found as many as 36 citations and partial reduplication was found as many as 12 quotations.